Evaluation of Newborn Hearing Screening Programs in Riyadh, Saudi Arabia: A Mixed Methods Study - Ahmad A. Alanazi; Noura I. Alothman; Mohammed F. AlHarbi; Alanood Alkhalaf; Alshima Almsened; Manar Alzahrani; Hana Alsawaji (Journal of Nature and Science of Medicine)
Background: Newborn hearing screening (NHS) programs were established globally to reduce the negative consequences of hearing loss. Limited information is available about NHS programs in Riyadh and Saudi Arabia generally. This study explored how NHS programs are conducted in healthcare settings for quality assurance. Methods: The concurrent triangulation mixed methods design was used to gather data from the supervisors of NHS programs who were invited to answer a questionnaire and set for a structured interview. The questionnaire consisted of two categories: the facility and test personnel, and the test protocol. The structured interview included two questions about these programs’ opportunities and challenges. Results: Data were collected from 24 participants who represented 11 public and 13 private healthcare facilities in Riyadh. The results showed that nurses were the most test personnel who were primarily trained by audiologists. Less than half of NHS programs were supervised by audiologists. The combination of otoacoustic emissions and automated auditory brainstem responses was the most used test protocol. More than half of newborns who failed the first NHS were referred to audiology clinics within a month of the first screening. Most test personnel were not trained on how to counsel parents. The interview resulted in one core category, three themes, and 15 subthemes. Low parental awareness about the NHS was identified, with suggestions to educate parents on the NHS before and after the screening. Not all insurance companies include NHS in all their insurance classes. Conclusions: Establishing a tracking system and standardizing test protocols with a surplus of test personnel and equipment were identified as areas for improvement. The Council of Health Insurance in Saudi Arabia is recommended to include NHS as a mandatory screening for all patients in the private sector, either covered by insurance or cash-pay patients.